Online Healthcare Community Interaction Dynamics - Xitong Guo; Shanshan Guo; Douglas Vogel; Yijun Li (Journal of Management Science and Engineering, 2016)
Abstract:: With the increasing dilemma of the rapid global demand for healthcare services (often in the presence of limited resources), how to creatively allocate and use healthcare resources across a widespread population has become a salient issue. Online healthcare communities (OHCs) are regarded as a potential ICT-based partial solution. In contrast to traditional healthcare, online doctor-patient interaction is unlimited in terms of time and space limitations while an OHC is exposed to the whole community. These characteristics are key to achieving synergistic doctor-patient interaction and community development in the longer term. In order to explore the nature of doctor-patient interaction dynamics in an OHC, we systematically investigate doctor-patient interaction dynamics from the dual perspectives of doctor and patient. Our doctor-patient interaction dual-cycle model has been built based on six doctor-patient interaction processes (i.e., searching, choosing, knowledge sharing, providing, receiving and balancing). According to our dual-cycle model, four key managerial issues in OHC (information asymmetry, incentive mechanisms, service delivery processes and interaction mechanisms) have been identified as examples. Discussion and directions for future research, with challenges as well as opportunities, have been elaborated. A broad view with fruitful research potential is ensured and new theories and methods ultimately provide implications for effectively and efficiently allocating scarce healthcare resources to a broader population. Keywords:: Online Healthcare Community, Doctor-Patient Interaction, Dual-Cycle Model, Interaction Dynamics, Incentive Mechanisms